Community Behavior in Waste Management on the Beach of Rumahtiga Village, Teluk Ambon District, Ambon City - Salakory, Melianus; Riry, Johan; Luanmasar, Indah Eklesya (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Education is a life experience that arouses interest in learning and teaching something already known. Education lasts forever (lifelong education), meaning that every activity from birth to death is educational. School quality is reflected not only in efficiency and the school environment, starting from school administration, namely school governance. School principals, staff, and teachers are responsible for students' physical and spiritual comfort. This study aims to determine the effect of the school's physical environment, non-physical environment, and physical and non-physical environment on students' learning interest in West Seram State Senior High School 7. This study uses a quantitative approach. The results of this study show that the physical environment, non-physical, as well as physical and non-physical together have a significant effect on students' interest in learning at West Seram State Senior High School 7